Use of solid-phase PCR for enhanced detection of airborne microorganisms. - Alvarez, A J (1994)
The solid-phase PCR (SP-PCR) was compared with a culture-based technique for the detection of aerosolized Escherichia coli DH1. Results with SP-PCR showed an increase in detection sensitivity over that of culture methods. Therefore, SP-PCR may be useful for the detection of airborne microorganisms which may be nonculturable because of aerosolization or sampling stress.